Proses Analisis dalam Perbaikan Algoritma Line Maze Solving untuk Jalur Lengkung dan Zig-zag - Musridho, Raja Joko; Yanto, Febi; Gusman, Deddy (Jurnal Inovasi Teknik Informatika, 2021)
Line Maze Solving algorithm is an algorithm for line follower robot that is used on maze with right angle intersections. Previous work has improved the algorithm so that it can be used for the maze with curved and zig-zag intersections. The improvement was done because the algorithm only recognizes right angle intersections. This research presented the analysis process of the improvement of the algorithm in details, hence the difference between Line Maze Solving algorithm before and after the improvement can be seen clearly.